2018
DOI: 10.12697/poa.2018.27.1.01
|View full text |Cite
|
Sign up to set email alerts
|

T-2 mycotoxin induced apoptosis in broiler’s liver tissue

Abstract: Apoptosis is a process of programmed cell death that occurs in multicellular organisms. As T-2 toxin is known to induce apoptosis in mammalian cells, the aim of the present experiment was to study the toxic effect of T-2 on chicken liver tissue using apoptosis-related antibodies p21 and p53 which are involved in the p53/p21-mediated apoptotic signalling pathway.The experiment was conducted on fourteen 40-day-old broilers (Gallus gallus domesticus) who were divided into control and T-2 toxin groups. For the T-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Therefore, we confirmed that mycotoxins demonstrate an inhibitory effect on the growth of hepatocytes cells, thereby causing damage and promoting apoptosis in hepatocytes cells. The molecular mechanisms that are involved were explored, and the OTA and AFB1 had synergistic cytotoxic effects by inducing apoptosis in the liver cells [ 16 , 17 ]. Wang et al [ 17 ] reported that the OTA could increase cell apoptosis in cultured hepatocytes (PHHs) and Kupffer cells (HKCs), and it could possibly activate the JNK signal pathway mechanism and affect the expression of caspase-3, Bax, and Bcl-2 in cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we confirmed that mycotoxins demonstrate an inhibitory effect on the growth of hepatocytes cells, thereby causing damage and promoting apoptosis in hepatocytes cells. The molecular mechanisms that are involved were explored, and the OTA and AFB1 had synergistic cytotoxic effects by inducing apoptosis in the liver cells [ 16 , 17 ]. Wang et al [ 17 ] reported that the OTA could increase cell apoptosis in cultured hepatocytes (PHHs) and Kupffer cells (HKCs), and it could possibly activate the JNK signal pathway mechanism and affect the expression of caspase-3, Bax, and Bcl-2 in cell death.…”
Section: Discussionmentioning
confidence: 99%
“…fungus is known to induce apoptosis in mammalian cells. Trichothecene mycotoxin causes acute and chronic toxicity and induces apoptosis in the immune system and liver tissues, especially AFB1 and OTA [ 8 , 16 ]. In addition, OTA exhibits a cytotoxic effect on the mucosa-associated lymphoid tissue and intestinal epithelium, which alters the intestinal barrier and increases the animal’s susceptibility to various related diseases that cause to a reduced rate of nutrient absorption [ 17 ].…”
Section: Introductionmentioning
confidence: 99%